Imperialism as diaspora : race, sexuality, and history in Anglo-India - Crane, Ralph J., 1957- (Postcolonialism across the disciplines., 2013)
Imperialism as Diaspora reassesses the important years of the British Raj in India and the diasporic position of Anglo-Indians, who, while neither quite British nor Indian, were simultaneously both, and who were instrumental in the construction of the Empire in India.